2015
DOI: 10.17979/reipe.2015.0.05.189
|View full text |Cite
|
Sign up to set email alerts
|

Actividad física y deporte extraescolar: rendimiento escolar e índice de masa corporal (IMC)

Abstract: Objetivos: Conocer el perfil deportivo y educativo de la población y establecer la relación existente entre la Actividad Física y Deporte Extraescolar y el Índice de Masa Corporal (IMC) y las Notas Académicas. Material y Método: Se trata de un estudio, descriptivo, transversal, realizado sobre una población diana de 62 sujetos, de entre 6 y 12 años, a quienes se les aplicó un Cuestionario -que indagaba acerca de Variables de Identificación Familiares, Educativas, IMC y relacionadas con la Actividad Física y De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…In this section we introduce some notations that are frequently used in this paper. We will mainly follow the presentation of Cao and Titi [10].…”
Section: Notationsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this section we introduce some notations that are frequently used in this paper. We will mainly follow the presentation of Cao and Titi [10].…”
Section: Notationsmentioning
confidence: 99%
“…However, only a few papers deal with the rate of convergence, see [10,15]. In [10] the rates of convergence of four α-models (NS-α model, Leray-α model, modified Leray-α model, and simplified Bardina model) in the two-dimensional (2D) case, subject to periodic boundary conditions on the periodic box [0, L] 2 are studied. The authors of [10] mainly showed that all the four α-models have the same order of convergence and error estimates; that is, the convergences in the L 2 -norms are all of the order O α L log( L α ) 1 2 as α L tends to zero, while in [15] the rate of convergence of order O(α) is obtained in a mixed L 1 − L 2 time-space norm with small initial data in Besov-type function spaces.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations